PENJADWALAN PERAWATAN MESIN DISTILASI MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE II DENGAN PENDEKATAN OVERALL EQUIPMENT EFFECTIVENESS - Ajeng Puspita Sari (2022)
UPN Veteran Jakarta's Laboratory has a Distillation Machine that has not been used for 2 years. In this machine, it was found that there was corrosion which made the container in this machine get humidity which caused small holes that caused leaks, decreased surface appearance quality, contaminated the product, and decreased engine performance. Researchers need to test the effectiveness of the distillation machine using Overall Equipment Effectiveness and make a maintenance schedule and replacement of critical components using the Reliability Centered Maintenance II. The OEE value of the Distillation Machine is 51%. The highest losses are in Idling and Minor Stoppages Losses with a percentage of 45%. The critical components of the Distillation Machine are the Condenser and Water Tank. The schedule for checking the condenser component is 6 hours and the water tank component is 3 hours. The schedule for replacing the condenser and water tank components is 200 hours. The condenser component is obtained for prevention costs of Rp.8.559.631, while the cost of damage is Rp.8149.416. For the tub component, the prevention cost is Rp.1.606.879, while the cost of damage is Rp.1.296.584.